Relative fundamental frequency during vocal onset and offset in older speakers with and without Parkinson's disease - Stepp, Cara E. (Acoustical Society of America, 2013)
The relative fundamental frequency (RFF) surrounding production of a voiceless consonant has previously been shown to be lower in speakers with hypokinetic dysarthria and Parkinson's disease (PD) relative to age/sex matched controls. Here RFF was calculated in 32 speakers with PD without overt hypokinetic dysarthria and 32 age and sex matched controls to better understand the relationships between RFF and PD progression, medication status, and sex. Results showed that RFF was statistically significantly lower in individuals with PD compared with healthy age-matched controls and was statistically significantly lower in individuals diagnosed at least 5 yrs prior to experimentation relative to individuals recorded less than 5 yrs past diagnosis. Contrary to previous trends, no effect of medication was found. However, a statistically significant effect of sex on offset RFF was shown, with lower values in males relative to females. Future work examining the physiological bases of RFF is warranted.